2006
DOI: 10.1002/app.24131
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene–nanosilica‐filled composites: Effects of epoxy‐resin‐grafted nanosilica on the structural, thermal, and dynamic mechanical properties

Abstract: This article reports a comparative study of polypropylene (PP) nanocomposites synthesized with nanosilica (NS) and diglycidyl ether of bisphenol A, an epoxyresin-grafted nanosilica (ENS), as nanofillers. These nanocomposites were prepared with the melt-mixing method at a constant loading level of 2.5 wt %; this loading level was much lower than that used for fillers in conventional composites. The effects of pure NS and ENS on the thermal, structural, mechanical, and dynamic mechanical properties of PP were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…When COOH-MWCNTs are introduced into system, there would, on the one hand, result in a decrease in thermal stability, which can be due to the weakened Van der Waals interaction between polymer chains [25] and the lowered T g shown in Table 3. On the other hand, the addition of COOHMWCNTs can also increase the thermal stability due to their hindering effect to the thermal motion of polymer molecular chains [26]. However, the final result of COOH-MWCNTs on the thermal stability, arising from the antagonistic competition of these two effects, is that the addition of COOHMWCNTs slightly improves the thermal stability of DGEBA/EMI-2,4 system.…”
Section: Resultsmentioning
confidence: 99%
“…When COOH-MWCNTs are introduced into system, there would, on the one hand, result in a decrease in thermal stability, which can be due to the weakened Van der Waals interaction between polymer chains [25] and the lowered T g shown in Table 3. On the other hand, the addition of COOHMWCNTs can also increase the thermal stability due to their hindering effect to the thermal motion of polymer molecular chains [26]. However, the final result of COOH-MWCNTs on the thermal stability, arising from the antagonistic competition of these two effects, is that the addition of COOHMWCNTs slightly improves the thermal stability of DGEBA/EMI-2,4 system.…”
Section: Resultsmentioning
confidence: 99%
“…Reddy et al manufactured polypropylene (PP)/nano-silica (NS) nanocomposites [56]. The modulus of PP-NS was much higher than that of pure PP, and that of PP-ENS (epoxy-resin-grafted nano-silica) was higher than that of pure PP, but lower than PP-NS.…”
Section: Properties Of Polymer-based Nanocompositesmentioning
confidence: 99%
“…The agglomerated particles can not impose any restrictions on molecular mobility, and thereby resulting in a lower T g . Previous studies 7,8 suggested that high thermal stability of polymers in the presence of fillers is due to the hindered thermal motion of polymer molecular chains. Chemical bonds established between nano-SiC particles and epoxy strengthen the interface interaction, which would restrict the thermal motion of epoxy resin chains, and therefore, on the other hand, the addition of nano-SiC particles can also increase the thermal stability.…”
mentioning
confidence: 99%
“…Studies have shown that the performance of polymeric materials can be improved by adding a small amount (<5 wt %) of inorganic nanofillers without compromising weight or processability of the composites. [2][3][4][5][6][7][8] The challenges are to obtain remarkable improvements in the interfacial bonding between polymer matrix and nanofillers. Stronger interfacial bonding will impart better properties.…”
mentioning
confidence: 99%